Participation of fibroblast growth factor-1 and interleukin-10 in connective tissue repair following subcutaneous implantation of bioceramic materials in rats - Delfino, Mateus Machado [UNESP]; Jampani, José Leandro de Abreu [UNESP]; Lopes, Camila Soares [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Tanomaru-Filho, Mário [UNESP]; Sasso-Cerri, Estela [UNESP]; Cerri, Paulo Sérgio [UNESP] (Wiley, 2023)
Aim: To evaluate whether the bioceramic materials Bio-C Pulpo (Bio-C, Angelus) and mineral trioxide aggregate (MTA) Repair HP (MTA-HP, Angelus) induce fibroblast proliferation and release of interleukin-10 (IL-10), an anti-inflammatory cytokine, stimulating connective tissue remodelling. The tissue response of Bio-C and MTA-HP was compared with the White MTA (WMTA; Angelus) since studies have demonstrated that WMTA induces tissue repair. Methodology: Bio-C, MTA-HP and WMTA were inserted into polyethylene tubes and implanted in the subcutaneous tissue of Holtzman rats for 7, 15, 30 and 60 days. As a control group (CG), empty tubes were implanted subcutaneously. The number of fibroblasts (FB), Ki-67-, fibroblast growth factor-1- (FGF-1) and IL-10-immunolabelled cells and collagen content in the capsules was obtained. The data were subjected to two-way anova followed by Tukey's test (p ≤.05). Results: At 7 days, significant differences in the number of FB were not detected amongst Bio-C, MTA-HP and WMTA groups (p ˃.05). The capsules of all groups exhibited a significant increase in the number of FB and content of collagen over time. From 7 to 60 days, a significant reduction in the number of FGF-1- and Ki-67-immunolabelled cells was seen in the capsules of all specimens. In all periods, no significant difference in the number of FGF-1-immunolabelled cells was detected between Bio-C and CG specimens. At 60 days, significant differences in the immunoexpression of FGF-1 were not observed amongst the groups. At 7 and 15 days, the highest immunoexpression for Ki-67 was present in Bio-C specimens whilst, after 30 and 60 days, no significant difference was observed amongst the bioceramic materials. At 7 days, few IL-10 immunolabelled cells were present in the capsules of all specimens whereas, at 60 days, a significant increase in the IL-10-immunostaining was present in all groups. At 60 days, the Bio-C, MTA-HP and WMTA groups showed a greater number of IL-10-immunolabelled cells than in the CG specimens (p <.0001). Conclusions: Bio-C, MTA-HP and WMTA stimulate fibroblast proliferation, leading to the formation of collagen-rich capsules. FGF-1 and IL-10 may mediate the remodelling of capsules around Bio-C, MTA-HP and WMTA bioceramic materials.
Keywords: bioceramic materials; cell proliferation; collagen; immunohistochemistry; interleukin-10; Ki-67